Efficacy and safety of the dual bronchodilator combination umeclidinium/vilanterol in COPD by age and airflow limitation severity: A pooled post hoc analysis of seven clinical trials. (August 2019) - Ray, Riju; Tombs, Lee; Naya, Ian; Compton, Chris; Lipson, David A.; Boucot, Isabelle
Abstract: Background: Elderly patients with chronic obstructive pulmonary disease (COPD) and those with more severe airway limitation are perceived to experience reduced efficacy from inhaled bronchodilators, especially those administered in a dry powder inhaler. This study compared the efficacy and safety of a long-acting muscarinic antagonist/long-acting β2 -agonist dry powder combination in elderly patients with COPD and patients with moderate-to-very severe airflow limitation. Methods: This post hoc pooled analysis of seven randomized studies of ≥12 weeks' duration investigated the efficacy and safety of umeclidinium/vilanterol (UMEC/VI) 62.5/25 μg versus tiotropium (TIO) 18 μg or fluticasone propionate/salmeterol (FP/SAL) 250/50 μg. Change from baseline in trough forced expiratory volume in 1 s (FEV1 ), a common efficacy measure in all trials, proportion of FEV1 responders (≥100 mL increase from baseline) and safety outcomes were analyzed at Day 28, 56, and 84 in patients classified by age (<65, ≥65, and ≥75 years of age) and severity of baseline airflow limitation (Global initiative for chronic Obstructive Lung Disease [GOLD] stage 2 [moderate] and stage 3/4 [severe/very severe]). A 24-week analysis was also conducted for the UMEC/VI versus TIO comparison. Results: The pooled intent-to-treat population comprised 3821 patients (≥65 years: 44–45%; ≥75 years: 9–10%; GOLD stage 3/4: 50–55%); 2246, 874, and 701 patients received UMEC/VI, TIO, or FP/SAL, respectively. Significant improvements in trough FEV1 at Day 84 were observed with UMEC/VI versus TIO or FP/SAL irrespective of age (all p ≤ 0.029) or GOLD stage (all p < 0.001). The proportion of FEV1 responders at Day 84 was significantly greater with UMEC/VI versus TIO or FP/SAL across all age groups (all p ≤ 0.016) and GOLD stages (all p < 0.001). Safety profiles were similar between treatment groups. Conclusion: UMEC/VI consistently demonstrated improved lung function versus TIO and FP/SAL across age and airflow limitation severity subgroups, with no safety concerns, indicating that UMEC/VI provides no loss in efficacy or additional safety concerns for both elderly patients with COPD and patients with severe/very severe airway limitation.